COMPARATIVE STUDY OF THE CESIUM UPTAKE ABILITY BETWEEN HEU-TYPE (CLINOPTILOLITE-HEULANDITE) ZEOLITIC TUFF AND PURE HEULANDITE - Mytiglaki, Christina; Kantiranis, Nikolaos; Misaelides, Panagiotis; Noli, Fotini; Filippidis, Anestis (Bulletin of the Geological Society of Greece, 2020)
Specific continuous layers of zeolitic tuff in Ntrista stream location of Petrota area of Evros region (NA11) and pure natural crystals of heulandite (HEU1) from the collection of the Department of Mineralogy-Petrology-Economic Geology, School of Geology, Aristotle University of Thessaloniki, have been investigated. The X-Ray Diffraction analyses showed that the sample NA11 consists of 86 wt% HEU-type zeolite, 4 wt% micas+ clay-minerals, 4 wt% quartz, 2 wt% christobalite and 4 wt% feldspars, while the sample HEU1 is pure heulandite crystal. The mineral-chemistry was determined by SEM-EDS microanalyses. The zeolite of the NA11 sample is Ca-rich clinoptilolite and its chemical formulae is Ca1.8K1.0Mg0.7Na0.5Al6.4 Si29.5O72·21H2O, while the zeolite of the sample HEU1 is heulandite and its chemical formulae is Ca3.6Na1.0Κ0.2Sr0.2Ba0.1Al8.1Si27.6O72·21H2O. The uptake ability of the samples was measured by the AMAS method (Ammonium Acetate Saturation). The two examined materials show high uptake ability. The measured value for the zeolitic tuff NA11 is 231 meq/100g, while for the heulandite crystal (HEU1) is 296 meq/100g. For the determination of the cesium sorption a CsNO3 solution (concentration 500 mg/L), labelled with small activity of 137Cs, and pH 2-12 was used. The sorption of the cesium by the two materials, was determined by measuring the gamma radiation emitted by the 137Cs tracer. The zeolitic tuff presents higher uptake ability of radioactive cesium than the pure heulandite crystal, whereas the sorption of radioactive cesium is not significantly affected by the pH values of the initial solutions in the range pH 2-12.The clinoptilolitic zeolitic tuff NA11 is suitable material for various environmental, agricultural and industrial applications.